Monitoring invisible corrosion in concrete using a combination of wave propagation techniques - Sharma, A.; Sharma, S.; Sharma, S.; Mukherjee, Abhijit (Elsevier BV, 2018)
The paper reports two non-destructive techniques based on wave propagation for monitoring onset of corrosion in concrete before it is visible. Reinforced concrete beam specimens were subjected to anodic corrosion at a constant voltage. The specimens were instrumented with surface mounted Acoustic Emission (AE) sensors to record acoustic events inside the specimens due to corrosion. They were also monitored using the Ultrasonic Guided Waves (UGW) technique by passing an ultrasonic pulse through the bar. The results are correlated with well-established electrochemical techniques. From simultaneous monitoring of corrosion using the three technologies pros and cons of each technology have been determined. It can be concluded that a judicious combination of electrochemical and wave technologies can reveal the state of corrosion from its early stages.